OP0102 Genetic Effects on Trabecular and Cortical Volumetric Bone Mineral Densities and Bone Microstructure Measured by Hrpqct. (15th July 2016) - Pan, F.; Squibb, K.; Thomson, R.; Winzenberg, T.; Zebaze, R.; Jones, G.
Abstract : Background: While both genetic and environmental factors affect areal BMD (aBMD), as much as 80% of variation in BMD is attributable to genetic factors [1]. aBMD measured by dual x-ray absorptiometry (DXA) is used as a surrogate measure for bone strength and is the gold standard for diagnosis of osteoporosis. However, structural abnormalities independent of aBMD may contribute to bone fragility. Bone structural parameters quantified using high-resolution pQCT (HRpQCT) may help more accurately identify individuals at risk for fracture than aBMD alone [2]. The heritability of cortical and/or trabecular bone microstructure determined by HRpQCT are unknown. Objectives: To estimate heritability of trabecular density (TD), cortical density (CD), trabecular thickness (TT) and cortical thickness (CT) at tibia and radius measured by HRpQCT and investigate the genetic correlations of these between the tibia and radius. Methods: Participants were 174 mother-child pairs from 161 families (161 mothers, mean age 52 years; 174 children, mean age 26 years). Cortical and trabecular bone microstructure at tibia and radius were measured by HRpQCT. SOLAR software was used to conduct quantitative genetic analyses with adjustment for covariates. Results: In multivariable analysis, maternal tibial TD, CD, TT and CT were independently associated with all corresponding bone microstructures in the children (β=0.14 to 0.37, all P<0.05) after adjustment for age, sex, weight, height, smoking history and physical activity. Additive genetic factors explained 67%, 36%, 33% and 46% of the variation in TD, CD, TT and CT, respectively (adjusted P<0.05). Similar results were observed at the radius, but the heritability estimates were lower than that at tibia (range, 12%>57%). Genetic correlations for TD and TT between tibia and radius (rg =0.80 for TD; 0.86 for TT) were greater than that of CD and CT (rg =0.47 for CD; 0.50 for CT). Conclusions: Genetic factors appear to have an important role in the development of peak bone microarchitecture and are partly shared for the tibia and radius. The heritability estimates of radius were lower than that of tibia, suggesting tibia is affected by environmental factors to a greater extent than radius, possibly due to more loading at tibia. References: Peacock M, Turner CH, Econs MJ, Foroud T: Genetics of osteoporosis. Endocr Rev 2002; 23:303–26. Zheng HF, Tobias JH, Duncan E, Evans DM, Eriksson J, Paternoster L et al: WNT16 influences bone mineral density, cortical bone thickness, bone strength, and osteoporotic fracture risk. PLoS Genet 2012; 8:e1002745. Disclosure of Interest: None declared